HGTree v2.0: a comprehensive database update for horizontal gene transfer (HGT) events detected by the tree-reconciliation method. Issue Volume 51:Issue D1(2023) (9th November 2022) - Choi, Youngseok; Ahn, Sojin; Park, Myeongkyu; Lee, SaetByeol; Cho, Seoae; Kim, Heebal
Abstract: HGTree is a database that provides horizontal gene transfer (HGT) event information on 2472 prokaryote genomes using the tree-reconciliation method. HGTree was constructed in 2015, and a large number of prokaryotic genomes have been additionally published since then. To cope with the rapid rise of prokaryotic genome data, we present HGTree v2.0 (http://hgtree2.snu.ac.kr ), a newly updated version of our HGT database with much more extensive data, including a total of 20 536 completely sequenced non-redundant prokaryotic genomes, and more reliable HGT information results curated with various steps. As a result, HGTree v2.0 has a set of expanded data results of 6 361 199 putative horizontally transferred genes integrated with additional functional information such as the KEGG pathway, virulence factors and antimicrobial resistance. Furthermore, various visualization tools in the HGTree v2.0 database website provide intuitive biological insights, allowing the users to investigate their genomes of interest.